Cyanobacterial control in natural water bodies by commercially available ultrasound: biomass reduction and cyanotoxin degradation - Aleksandra Krivograd Klemenčič; Tina Eleršek (Acta Biologica Slovenica)
Low-frequency and low-intensity commercially available ultrasound to control algal growth in natural water bodies was studied. To evaluate the efficiency of ultrasound on cyanobacteria biomass removal and microcystins release and degradation a large-scale lab experiment with 150 L of high density Microcystis aeruginosa suspension simulating natural conditions was conducted at different times of ultrasonication: 0, 15 min, 1 h, 5 h, 24 h, and 48 h. The first effect of ultrasonication on biomass reduction was evident at 24 h of continuous ultrasonication with the highest removal rates of 97% and 93% for cell count and chlorophyll a, respectively, at 48 h of continuous ultrasound treatment. The growth inhibition test showed biomass reduction in the samples exposed to ultrasonication for at least one hour with increasing effect from here on. The most efficient in M. aeruginosa reduction was the longest tested ultrasound treatment of 48 h with the growth inhibition of 96%, followed by 24-h ultrasound treatment with 50%, and 5-h ultrasound treatment with 17% growth inhibition after 9 days of incubation. At five hours of ultrasonication a sharp increase in dissolved microcystins in the medium was observed as a result of ultrasound induced stress followed by drop of dissolved microcystins under detection limit at 24 h of continuous ultrasonication. This study showed that commercially available ultrasound devices are highly efficient for cyanobacterial bloom control already at relatively low times of exposure, one to two days, with no health risks due to increased dissolved toxins after continuous ultrasound treatment for 24 h or more.